If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -84 = -7(8 + -4K) -84 = (8 * -7 + -4K * -7) -84 = (-56 + 28K) Solving -84 = -56 + 28K Solving for variable 'K'. Move all terms containing K to the left, all other terms to the right. Add '-28K' to each side of the equation. -84 + -28K = -56 + 28K + -28K Combine like terms: 28K + -28K = 0 -84 + -28K = -56 + 0 -84 + -28K = -56 Add '84' to each side of the equation. -84 + 84 + -28K = -56 + 84 Combine like terms: -84 + 84 = 0 0 + -28K = -56 + 84 -28K = -56 + 84 Combine like terms: -56 + 84 = 28 -28K = 28 Divide each side by '-28'. K = -1 Simplifying K = -1
| 8y-12-3y=-2 | | 9x+8y=-16 | | 4(4x-3)=8(2x-2)+4 | | 9n-20=7 | | 6x-10=3x+5 | | 42y-7=31 | | 54=4w+2w | | 90×2/3 | | M^2+56=15m | | 54=4w | | x-3=-2+3 | | 2*x+3=5*x+17 | | 5(n-1)=55 | | 3x+5.4=(-6.3) | | 8x+y=240 | | 5y-17=-2 | | 5x/5y | | 10+11y+3y^2=0 | | 8-x=-2x+16 | | 6x+9=-6x-81 | | 2x^2+15x-2=0 | | a=17-b | | f(11)=2(11)+4 | | N/3-8=16 | | 8x+9y=96 | | f(11)=2x+4 | | (3^×)(9^2x)=1^3/9 | | y=0.25x+8 | | 5x+20+2x+11=115 | | 14n+3(n+5)=117 | | x^1/4(2x^3/4-x^1/4) | | (5v-3)(5v-2)=0 |